PERANAN GURU PENDIDIKAN ISLAM DALAM PEMBINAAN SAHSIAH PELAJAR: SATU TINJAUAN AWAL TERHADAP GURU PENDIDIKAN ISLAM DI DAERAH MARANG, TERENGGANU: THE ROLE OF ISLAMIC EDUCATION TEACHER IN THE CONSTRUCTION OF STUDENT’S MORAL: A PRELIMINARY STUDY ON ISLAMIC EDUCATORS IN MARANG, TERENGGANU - Ahmad, Syafiqah Solehah; Tengku Kasim, Tengku Sarina Aini (Journal of Islamic Educational Research, 2017)
Nowadays various issues regarding the character of a student in a school give a negative impact on the teacher profession generally and Islamic Education Teacher specifically. Some recent studies have shown that Muslim students are trapped by the phenomenon of social phenomena, moral collapse and personality. The moral and morality crisis of students is said to have a close relationship with Islamic Education Teachers who have a role as a moral educator and personality of the students. This paper is also written to dismantle the role of Islamic Education Teachers as well as to see the problems and challenges arising in the realization of their role as Murabbi, Mu’allim, Mu’addib, Mudarris and Murshid and those who can be role models and examples of noble personality among students include from the context of building personality and character. Islamic Education Teachers should be prepared to carry out their duties and responsibilities as well as overcome obstacles, challenges and issues that arise.